Relationship between SLCO1B3 and ABCA3 polymorphisms and imatinib response in chronic myeloid leukemia patients. Issue 3 (April 2015) - de Lima, Luciene Terezina; Bueno, Carolina Tosin; Vivona, Douglas; Hirata, Rosario Domiguez Crespo; Hirata, Mario Hiroyuki; Hungria, Vania Tiestsche de Moraes; Chiattone, Carlos Sérgio; Zanichelli, Maria Aparecida; Chauffaille, Maria de Lourdes Lopes Ferrari; Guerra-Shinohara, Elvira Maria
Abstract : Background: Genetic variations in membrane transporters may contribute to imatinib mesylate (IM) resistance in chronic myeloid leukemia (CML). Objective: To investigate the relationship between SLCO1B3, SLCO1A2, and ABCA3 polymorphisms and IM response in CML patients. Methods: Patients in chronic phase CML ( N = 118) were studied. All patients were treated with a standard dose of IM (400 mg/day) and classified into one of the two groups according to their responses. Major molecular response (MMR) and complete molecular response (CMR) were evaluated. Criteria for response failure were established according to European LeukemiaNet (2009). Analysis of the SLCO1B3 c.334T > G (rs4149117) and c.699G > A (rs7311358), SLCO1A2 c.516A > C (rs11568563) and c.-62-361G > A (rs3764043), and ABCA3 c.1755C > G (rs323043) and c.4548-191C > A (rs150929) polymorphisms was carried out by real-time polymerase chain reaction. Results: SLCO1A2 and ABCA3 polymorphisms have similar frequencies between responders and non-responders. SLCO1B3 699GG and 344TT genotypes were more frequent in the responder group (63.8%) than in the non-responder group (44.7%, P = 0.042). Furthermore, carriers of 699GA/AA and 334TG/GG genotypes presented a higher probability of not responding to the standard dose of IM (odds ratio: 2.17; 95% confidence interval: 1.02–4.64, P = 0.04). Poor CMR for ABCA3 4548-91C > A was observed in patients with the CC/CA genotype when compared to AA carriers in the responder group ( P = 0.014). Conclusions: SLCO1B3 699GG and 344TT genotypes are associated with non-response to IM, while ABCA3 4548-91 CC/CA genotypes are related to poor CMR in CML patients treated with standard-dose imatinib.